2013
DOI: 10.1007/s11255-013-0554-4
|View full text |Cite
|
Sign up to set email alerts
|

Second malignancies in long-term testicular cancer survivors

Abstract: Preliminary analyses indicate increased SM occurrence in patients with primary TC in comparison with the general population, and it also occurs in younger age at the time of SM diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…[16][17][18] On the other hand, the incidence of secondary malignancies among testicular germ cell tumor (TGCT) survivors is higher compared to the general population. 19 However, among all second cancers described, liver tumors are seldom reported.…”
Section: Review and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18] On the other hand, the incidence of secondary malignancies among testicular germ cell tumor (TGCT) survivors is higher compared to the general population. 19 However, among all second cancers described, liver tumors are seldom reported.…”
Section: Review and Discussionmentioning
confidence: 99%
“…A recent Slovakian study 18 retrospectively analyzed 1367 testicular cancer patients treated between 1970 and 2012 and found significantly higher incidence of second malignancies in that population. They were mostly abdominal or pelvic cancers regardless of treatment for primary testicular cancer, and occurred at a younger age in comparison with the general population.…”
Section: Review and Discussionmentioning
confidence: 99%
“…An increasing concern is the observation that, life threatening conditions such as second malignancy and cardiovascular disease, occur more frequently in TC patients than in the general population. Long-term monitoring of TC survivors is necessary for possibility of the development of late side effects of the treatment modalities [27,28].…”
Section: Tc -Testicular Cancermentioning
confidence: 99%
“…An increased risk for gastro-intestinal cancers, mainly CRC, pancreatic and gastric cancer, has also been described in childhood cancer survivors treated with platinum-based chemotherapy [8]. Other studies have also reported an increased incidence of CRC following TC treatment with a RR varying between 1.3 and 2.3 compared with the general population [9][10][11][12][13][14][15]. The risk of developing CRC remained significantly elevated for a long period after TC treatment with elevated risks reported even after 35 years [12,13,16].…”
Section: Introductionmentioning
confidence: 98%